الفجوة الغذائية بين ندرة الموارد وغياب الحوكمة "الدول العربية نموذجا". : The Food Gap between Scarcity of Resources and Lack of Governance, “Arab countries as a model.” - عيسات فضيلة; جزار مصطفى (Journal of North African Economies, 2025)
This study partly addresses the food gap in the Arab countries as a complex security problem, with problematic consequences for food security, by threatening the sustainability of the food supply on the one hand, and obstructing food supply routes on the other hand, which prompted the necessity of researching the background of this problem. Is it Is it a result of scarcity of resources or poor management. The study concluded that the food gap in the Arab countries is mainly linked to the problems posed by the concept of food security, and to the structural, structural and functional causes that the Arab countries are experiencing. In order to overcome this deficit, the Arab countries must be rational in managing the available resources and adopting incentive policies to make the private sector a key partner in achieving sustainable Arab food security.